2016
DOI: 10.3389/fmicb.2016.01500
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Virus Particles Using Nanopore-Based Resistive-Pulse Sensing Techniques

Abstract: Viruses have drawn much attention in recent years due to increased recognition of their important roles in virology, immunology, clinical diagnosis, and therapy. Because the biological and physical properties of viruses significantly impact their applications, quantitative detection of individual virus particles has become a critical issue. However, due to various inherent limitations of conventional enumeration techniques such as infectious titer assays, immunological assays, and electron microscopic observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 57 publications
0
73
0
Order By: Relevance
“…Besides genome particles quantification, there are other techniques that quantify the total physical particles. Due to the nanosize of these biotherapeutics, nanoparticle tracking analysis (NTA) and tunable resistive pulse sensing (TRPS) are techniques can be used not only for particles quantification but also characterization regarding size distribution [156,157]. NTA has also been used for stability studies of exosomes particles during storage at different temperatures [158].…”
Section: Analytics In Process Developmentmentioning
confidence: 99%
“…Besides genome particles quantification, there are other techniques that quantify the total physical particles. Due to the nanosize of these biotherapeutics, nanoparticle tracking analysis (NTA) and tunable resistive pulse sensing (TRPS) are techniques can be used not only for particles quantification but also characterization regarding size distribution [156,157]. NTA has also been used for stability studies of exosomes particles during storage at different temperatures [158].…”
Section: Analytics In Process Developmentmentioning
confidence: 99%
“…The characteristics of resistive pulse, the amplitude and duration, can therefore be used to describe the extent of viral particle deformation. While several groups have used nanopores for characterization of biological nanoparticles, such as exosomes and viruses , the possible deformation of these particles inside nanopores and the resultant effects on particle characterization have been widely neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed reviews about impedance pulse sensing can be found from other review papers. 41,[59][60][61][62][63] Despite the differences in analyte recognition principles, if an electrical biomarker sensing array is used, each array needs to differentiate signals from individual sensors/sensing channels via signal processing/multiplexing strategies. In this paper, we focus on reviewing various multiplexing strategies (i.e., spatial/time/frequency/codes/particle-based multiplexing) aiming at detection of various biomarkers (i.e., nuclear acids, macromolecular biomarkers/proteins, and cells).…”
Section: Electrical Biomarker Detection Methodsmentioning
confidence: 99%